Lunan a history of the Filipino built environments (NCCA, 2012)
The three-part video Lunan alludes to the condition on which environment is built as well as the process of making it ; the design of the interior, the planning of the city, and the cultivation of landscape. In this exploration of space in the Philippine context, the project foregrounds the environment or nature, as well as the agency of the people inhabiting to shape it, to built it, to engage in the myriad schemes of culture.